Endurance training on low-carbohydrate and grain-based diets: A case study - Rosenkranz, R. R.; Cook, C. M.; Haub, M. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
To illustrate the effects of low-carbohydrate (LC) and grain-based (GB) diets on body composition, biomarkers, athletic training, and performance in an elite triathlete. Methods: The athlete followed 2 dietary interventions for 14 d while maintaining a prescheduled training program. Pre- and postintervention measurements for each diet included plasma and serum samples, resting energy expenditure, body composition, and a performance bike ride. Results: Compared with the GB diet, the LC diet elicited more disruptions to training and unfavorable subjective experiences. Total cholesterol, HDL cholesterol, LDL cholesterol, ratings of perceived exertion, and heart rate were elevated on the LC diet. Blood insulin, resting lactate, postexercise lactate, and C-reactive protein were lowest on the LC diet. Conclusion: The LC diet resulted in both favorable and unfavorable outcomes. The primary observation was a disruption to scheduled training on the LC diet. Researchers should consider how the potential mediating effect of disruptions to training could influence pretest-posttest designs.